Anthropogenic light and noise affect the life histories of female Gryllus veletis field crickets. (9th May 2022) - Rebar, Darren; Bishop, Corey; Hallett, Allysa C
Abstract: Adaptive plasticity often offsets the negative effects of rapid environmental change. However, anthropogenic stressors like noise and artificial light at night (ALAN) are often unlike those environments experienced ancestrally, making the resulting responses of individuals potentially maladaptive or less predictable. Further uncertainty stems from few studies exploring how the two anthropogenic stressors may interact to influence individual responses. Here we reared female Gryllus veletis field crickets in traffic noise, ALAN, both, or neither to assess how each environment impacted their development, mating behaviors, and reproductive output. We first found that anthropogenic stressors influenced female development in three ways: those reared in ALAN took longer to reach adulthood, females reared in traffic noise were smaller as adults, and females reared in traffic noise lived longer than those reared in both anthropogenic stressors. We then documented pronounced effects on their behaviors and fitness. Females reared in noise in any capacity were more responsive to advertising males and mated with them faster, and females reared in any anthropogenic stressor retained spermatophores longer. Perhaps more significantly, any anthropogenic stressor reduced the lifetime fitness of females through reduced oviposition, hatching success, both, or reduced offspring size at hatching. However, we did not find decreased fitness of females reared with both anthropogenic stressors relative to those reared with just one. Our results highlight how novel anthropogenic stressors may impact populations, but whether individuals can adapt may depend on an interplay between development, mating behaviors, and reproductive output. Abstract : Human-induced environmental changes of traffic noise and artificial light at night negatively impact female field crickets. By rearing females in noise, light, both, or neither, we show that developing in any anthropogenic environment modifies development and/or mating behaviors in various ways, but those adjustments could not offset the costs to reproduction. Female fitness was negatively impacted through reduced egg laying, reduced egg hatching success, or fewer hatching offspring.